Multilayer design of CrN/MoN protective coatings for enhanced hardness and toughness - Postolnyi, B. O. (2017)
We report on CrN/MoN multilayer coatings, their structure, elemental and phase composition, residual stresses, mechanical properties and their dependence on deposition conditions. The hardness and toughness were considered as main parameters for improvement of the protective properties of coatings. Multilayers with varying bilayer periods, ranging from 40 nm to 2.2 mm, were obtained by using cathodic arc physical vapour deposition (Arc-PVD) on stainless steel substrate. The elemental analysis was performed using wavelength-dispersive X-ray spectroscopy (WDS). The surface morphology and cross-sections were analysed with scanning electron microscopy (SEM). The X-ray diffraction (XRD) measurements, including grazing incidence X-ray diffraction (GIXRD), in-plane diffraction analysis and electron backscatter diffraction (EBSD), were used for microstructure characterisation. Mechanical properties of deposited films were studied by measuring hardness (H) and Young's modulus (E) with micro-indentation, H/E and H3/E2 ratios were calculated. The dependences of internal structure and, hence, mechanical properties, on layer thickness of films have been found. Significant enhancement of hardness and toughness was observed with decreasing individual layer thickness to 20 nm: H = 38-42 GPa, H/E = 0.11